Impact of the COVID-19 pandemic on outpatient endocrinology consultation and teleconsultation in a Peruvian hospital - Lopez Huamanrayme, Eddy (2022)
Background:  The COVID-19 pandemic affected the continuity of face-to-face medical consultations, so strategies, such as teleconsultations, were implemented to close the gaps in care. The objective of this study was to describe the impact of the pandemic in the traditional endocrinology consultation at Hospital Nacional Alberto Sabogal Sologuren (Callao, Peru). Materials and methods: We carried out a descriptive study of analysis of secondary data, that was obtained from the Sistema de Salud Inteligente of the Social Security of Peru. Data from outpatient consultations between May 2019 and November 2021 were analyzed. Results: Due to the pandemic, the proportion of face-to-face consultations decreased from 100% (pre-pandemic period) to 29,4% (during the pandemic), while teleconsultations predominated after its implementation. More than 68% of patients were women, in face-to-face consultations the median age before and during the pandemic was 59 and 56 years, respectively, while in teleconsultations it was 58 years. Diabetes mellitus was the main reason for consultation (between 32,6% and 34,4% of all consultations), followed by hypothyroidism and nodular thyroid disease. During the pandemic, the proportion of consultations for hypothyroidism was higher in teleconsultations vs. face-to-face consultations (25,3% vs. 18%). Conclusions: During the pandemic, teleconsultations predominated over face-to-face consultation. There were no relevant differences in median age or predominant gender among patients before or during the pandemic. Diabetes mellitus was the main reason for consultation in general and during the pandemic consultations for hypothyroidism were higher in teleconsultation.